The Intersection of Values and Social Reproduction: Lessons from Cuba - Bridges, Jessica (Journal of Interdisciplinary Studies in Education, 2020)
This article will examine how various socialist values are promoted through the Cuban educational system. The voices represented vary generationally, racially, and gender. This research is not meant to generalize about all educational experiences in Cuba; rather, it represents a variety of experiences in the educational system. The research represented in this article was gathered in June 2015 in Havana, Cuba. This article begins with a brief historical background on education in Cuba after the triumph of the revolution in 1959, followed by data collection methods, representation of the data through vignettes and poetry, and finally an analysis of the diverse experiences through the framework of intersectionality. The primary finding was that Cuban society taught socialist values overtly within the educational system through school-based activities, such as the Junior Pioneers from the primary level, and through its emphasis on values formation as part of teacher training. The inculcation of these revolutionary values through the education system kept the revolutionary ideology alive across generations.